Expeditionary forces in the First World War - Beyerchen, Alan D. 1945-; Sencer, Emre (Palgrave Macmillan US, 2019)
Intro -- Contents -- Notes on Contributors -- List of Figures -- Chapter 1 Introduction: Concept and Themes -- What Was an Expeditionary Force in the Great War? -- Chapters and Themes -- Bibliography -- Chapter 2 A Tale of Two Expeditionary Forces: Religion and Race in the Dardanelles and France -- Limited Expedition: North African Muslims and the Dardanelles Campaign -- Expedition Across the Color Line: Race, France, and the AEF -- Conclusion -- Bibliography -- Chapter 3 Far from Home? Perceptions and Experiences of First World War Nurses and Their Patients -- Recreating "Home" in Overseas Hospital Wards -- Nursing "the Other" -- Conclusion -- Bibliography -- Chapter 4 The Enemy Lurking Behind the Front: Controlling Sex in the German Forces Sent to Eastern and Western Europe, 1914-1918 -- Sexual Encounters Between Soldiers and Civilians -- Regulating the Wartime Sex Trade -- Civilian Reform Efforts -- Conclusion -- Bibliography -- Chapter 5 Vietnamese Contingents to the Western Front, 1915-1919 -- The Recruiting Campaign and the Recruits -- The Recruiting Campaign in Indochina -- The Recruits: Volunteers or Forced Labor? -- The Journey to France -- In the Mist of War -- Experience on the Front Line -- Battle for Chemin des Dames -- In the Balkans -- The Enemy and the Allies -- After the Armistice -- Compensation, Expectation, and Disappointment -- Rebellious Sons of Indochina -- Conclusion -- Bibliography -- Chapter 6 Expeditionary Forces in the Shatterzone: German, British and French Soldiers on the Macedonian Front, 1915-1918 -- Geography and Space -- Macedonia as an Intercultural Meeting Ground -- Martial Races -- Macedonia as Backwards, and as the Orient -- Conclusion -- Bibliography -- Chapter 7 An Alliance of Competing Identities: Stereotypes and Hierarchies Among Entente Expeditionary Forces on the Western Front -- Bibliography.